Pengaruh Bauran Promosi Terhadap Keputusan Nasabah Menabung Simpeda pada Bank Kalsel Unit Gambut - Noor Imansyah; Emy Rahmawati; Maryono Maryono (JURNAL BISNIS DAN PEMBANGUNAN, 2015)
This research aims to examine partially and simultaneously influence of the promotion mix such as advertising, personal selling, sales promotion, publicity, and direct marketing on customer decision to save in Simpeda at Bank Kalsel Unit Gambut.The type of this research is explanation with survey method trough questionnaires and interviews. The Population in this study were all active customer accounts owner Simpeda were data on 30 September 2015 at Bank Kalsel Unit Gambut, with sample selection technique uses accidental sampling. The method of sampling was using Slovin formula, with a total sample of 207 people. Data were processed and analyzed using multiple linier regression.The result of this research shows the influence of advertising is 35,7% and the influence of publicity is 25,9%, which these variables have significant influence on decision to save. While the influence of personal selling is 7,4%, the influence of sales promotion is 1,3%, and the influence of direct marketing is -11,3%, which these variables have not significant influence on decision to save. Then the promotion mix (advertising, personal selling, sales promotion, publicity, and direct marketing) simultaneously has significant influence on customer decision to save in Simpeda at Bank Kalsel Unit Gambut. With Adjusted R Square of regression model value is 0,246 which means that decisions to save variable are influenced by promotion mix variable at 24,6 percent. And the rest is 75,4 percent are influenced by other variables that are not mentioned in this research.Keywords: promotion mix, decision to save